A novel decomposer-exploiter interaction framework of plant residue microbial decomposition - Miao, Youzhi; Wang, Wei; Xu, Huanhuan; Xia, Yanwei; Gong, Qingxin; Xu, Zhihui; Zhang, Nan; Xun, Weibing; Shen, Qirong; Zhang, Ruifu (Genome Biology, 2025)
Plant residue microbial decomposition, subject to significant environmental regulation, represents a crucial ecological process shaping and cycling the largest terrestrial soil organic carbon pool. However, the fundamental understanding of the functional dynamics and interactions between the principal participants, fungi and bacteria, in natural habitats remains limited. In this study, the evolution of fungal and bacterial communities and their functional interactions were elucidated during the degradation of complexity-gradient plant residues. The results reveal that with increasing residue complexity, fungi exhibit heightened adaptability, while bacterial richness declines sharply. The differential functional evolution of fungi and bacteria is driven by residue complexity but follows distinct trajectories. Fundamentally, fungi evolve towards promoting plant residue degradation and so consistently act as the dominant decomposers. Conversely, bacteria predominantly increase expression of genes of glycosidases to exploit fungal degradation products, thereby consistently acting as exploiters. The presence of fungi enables and endures bacterial exploitation. This study introduces a novel framework of fungal decomposers and bacterial exploiters during plant residue microbial decomposition, advancing our comprehensive understanding of microbial processes governing the organic carbon cycling.